2015
DOI: 10.1016/j.joca.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal biomechanical alterations in an ACLT rabbit model of early osteoarthritis

Abstract: ACLT led to a disorganization of the collagen framework at the early stage of OA development, which decreases the mechanical resistance of the menisci. GAG content increases in response to this degradation. All of these results demonstrate the strong correlation between matrix and mechanical alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
5
23
0
1
Order By: Relevance
“…Similar to articular cartilage, mechanical injuries can also alter the meniscus biomechanical properties, cause disorganisation of collagen network, tissue calcification and concomitant changes in GAG and collagen content (Katsuragawa et al , 2010; Kwok et al , 2014; Pauli et al , 2011; Sun et al , 2012). It was found that the changes in meniscus mechanical properties accompanied changes in the articular cartilage post ACLT; a significant loss (by almost a factor of two) of equilibrium and dynamic compressive stiffness in meniscus from the ACLT knee was observed at week 9, which is consistent with previous studies (Levillain et al , 2015). However, articular cartilage stiffness was significantly reduced at the earlier time point of 3 weeks post ACLT.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to articular cartilage, mechanical injuries can also alter the meniscus biomechanical properties, cause disorganisation of collagen network, tissue calcification and concomitant changes in GAG and collagen content (Katsuragawa et al , 2010; Kwok et al , 2014; Pauli et al , 2011; Sun et al , 2012). It was found that the changes in meniscus mechanical properties accompanied changes in the articular cartilage post ACLT; a significant loss (by almost a factor of two) of equilibrium and dynamic compressive stiffness in meniscus from the ACLT knee was observed at week 9, which is consistent with previous studies (Levillain et al , 2015). However, articular cartilage stiffness was significantly reduced at the earlier time point of 3 weeks post ACLT.…”
Section: Discussionsupporting
confidence: 91%
“…Inflammation has been shown to have a catabolic effect on meniscal GAG coverage . The relationship between GAG coverage and modulus is not fully understood, but some studies have suggested that GAG coverage is related to equilibrium modulus while others report no such relationship . In the current study, there was a similar decline noted between GAG coverage and equilibrium modulus in both models based on the injured versus control limbs.…”
Section: Discussionsupporting
confidence: 65%
“…Information of elastin fibers could hardly be collected from such images. A previous study showed a similar conclusion that elastin fibers were not detected in rabbit menisci and the signal of elastin was absent [19].…”
Section: Histological Analysis Of the Meniscisupporting
confidence: 52%
“…A multiphoton laser scanning microscope (FV1000MPE, Olympus, Japan) was used for observing the collagen microstructure. The excitation wavelength was set 850 nm [19], and two band pass filters (i.e., 420-460 nm and 495-540 nm) were used to acquire the second harmonic generation (SHG) from collagen and the two-photon excited fluorescence(TPEF) from cells and elastin. A 25X, 1.05 NA water immersion objective was used, and the image field was 508 × 508 µm 2 .…”
Section: Histological Analysismentioning
confidence: 99%